2021
DOI: 10.1016/j.neurol.2020.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Social and emotional cognition in patients with severe migraine consulting in a tertiary headache center: A preliminary study

Abstract: MBo participated in setting and planning the research project, data collection, data analysis, and writing of the article. RAB and FV in setting up and planning the research project, data collection, and writing of the article. GS, NN, MBe and EM participated in data analysis and writing of the article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 14 publications
4
16
0
Order By: Relevance
“…Importantly, we found that cognitive and affective subcomponents of ToM were affected in our sample of patients with CM, but the deficit was slightly greater for the cognitive aspect of ToM. Our results of impairment of both components of ToM abilities in CM are consistent with a previous finding on episodic migraineurs who showed poorer performance on mini-social cognition and emotional assessment (Bouteloup et al, 2021). It is noteworthy that, when evaluating affective ToM by RMET, we did not find any difference between chronic migraineurs and HC.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Importantly, we found that cognitive and affective subcomponents of ToM were affected in our sample of patients with CM, but the deficit was slightly greater for the cognitive aspect of ToM. Our results of impairment of both components of ToM abilities in CM are consistent with a previous finding on episodic migraineurs who showed poorer performance on mini-social cognition and emotional assessment (Bouteloup et al, 2021). It is noteworthy that, when evaluating affective ToM by RMET, we did not find any difference between chronic migraineurs and HC.…”
Section: Discussionsupporting
confidence: 91%
“…These findings would suggest that patients with CM could correctly respond to questions not requiring mentalizing abilities but could not handle a mismatch between a character’s intention and another’s expectations, as required in complex social interactions. Indeed, the difficulties in inferring others’ mental states should not be neglected in psychological and medical practice, as these could have a significant impact on the migraine patient’s social life (Bouteloup et al, 2021), and could be due to an inability to focus their attention on another person’s mental state in a context of persistent pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While we did not find any difference between patients and controls on the ability to recognize emotions, a lower ability to infer others' mental states was observed in patients with cLBP. Similar results (i.e., lower mentalizing performance) have been observed in patients suffering from chronic somatoform pain [47] and severe migraine [48]. Contrasting with our present findings, emotion recognition abnormalities have been reported in complex regional pain syndrome [49].…”
Section: Followingsupporting
confidence: 84%
“…Bouteloup et al conducted a study on 23 patients with a diagnosis of migraine, demonstrating that these patients present difficulties in inferring mental states compared to HCs. However, the study included a small cohort of patients with both episodic migraine and chronic migraine with and without medication overuse (13). To the best of our knowledge, studies on ToM and MOH have never been conducted.…”
Section: Introductionmentioning
confidence: 99%